Modification of the existing maximum residue level for triclopyr in kiwi. (13th July 2020) - ; Anastassiadou, Maria; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Arysta LifeScience Benelux submitted a request to the competent national authority in Greece to modify the existing maximum residue levels (MRLs) for the active substance triclopyr in kiwi fruits. The data submitted in support of the request were found to be sufficient to derive an MRL proposal for kiwi fruits. Adequate analytical methods for enforcement are available to control the residues of triclopyr in the plant matrix under consideration (i.e. high acid content commodity) at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of triclopyr according to the reported agricultural practice is unlikely to present a risk to consumer health.